PENGARUH AKUNTABILITAS DAN TRANSPARANSI PELAPORAN KEUANGAN TERHADAP KEPERCAYAAN MUZAKKI (STUDI KASUS PENGELOLAAN, FILANTROPI BADAN AMIL ZAKAT BMH KOTA JAMBI) - Eja Armaz Hardi; Nuri Alam Siregar; Marissa Putriana (EKSYA : Jurnal Ekonomi Syariah, 2023)
The research in this writing aims to discuss the effect of accountability and transparency of financial reporting on muzakki's trust in the Baitul Mal Hidayatulloh case study, in writing using quantitative research methods according to Sarmanu (2017) this method is to test the truth or falsity of a theory, to collect and analyze data by going through steps such as; observation, interviews, questionnaires and documentation. then the data collected is tested data. the results of this study indicate that; (1) the transparency of financial reports has a significant effect on the muzakki's trust in paying zakat in baitul maal Hidayatulloh. (2) accountability and transparency of financial reports together have an influence on the muzakki's trust in paying zakat in baitu maal hidayatullah. (3) financial openness a Social institutions are a must in this digital world, both in the form of print out laboratories or reports on the web and other digital media, because it creates strong confidence for benefactors that funds are properly managed.